Short and Long-Run Integration : Do Capital Controls Matter? - Kaminsky, Graciela; Schmukler, Sergio L. (World Bank, Washington, DC, 2014)
The authors study whether capital controls affect the link between domestic and foreign stock market prices and interest rates. To examine the characteristics of international market integration and the effects of capital controls in the short and long run, they apply band-pass filter techniques to data from six emerging economics during the 1990s. They find that markets seem to be linked more at longer horizons. Equity prices seem to be more connected internationally than interest rates. They also find little evidence that controls effectively segment domestic markets from foreign markets. And when they do, the effects seem to be short-lived. Moreover, the effects of controls on outflows do not seem to differ from those of controls on inflows. For example, controls on outflows in Venezuela during the 1994 crisis, and unremunerated reserve requirements in Chile and Colombia during a capital-inflow episode, seem to have shielded domestic markets at the most at very high frequencies. The degree of financial sophistication does not seem to affect the authors' conclusion on the insulation provided by capital controls. True, more developed financial markets, such as those in Brazil, are more closely linked to international markets than those in Colombia and Venezuela, which are far more illiquid. But capital controls do not seem to provide an extra cushion against international spillovers even in less developed markets.